2016
DOI: 10.1002/stem.2323
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin II Is Essential for Maintaining Stemness by Redox Regulation in Liver Cancer Cells

Abstract: Redox regulation in cancer stem cells (CSCs) is viewed as a good target for cancer therapy because redox status plays an important role in cancer stem-cell maintenance. Here, we investigated the role of Peroxiredoxin II (Prx II), an antioxidant enzyme, in association with maintenance of liver CSCs. Our study demonstrates that Prx II overexpressed in liver cancer cells has high potential for self-renewal activity. Prx II expression significantly corelated with expression of epithelial-cell adhesion molecules (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…Prdxs function as a protector of ESC stemness by opposing ROS during neurogenesis and Prdxs depletion leads to differentiation into neurons [47]. Prdx2 depletion attenuated stemness of CSCs in hepatocellular carcinoma [48]. Prdx3 depletion resulted in a smaller percentage of CD133 + cells, a significant reduction in sphere formation, and enhanced sensitivity to 5-FU [46].…”
Section: Discussionmentioning
confidence: 99%
“…Prdxs function as a protector of ESC stemness by opposing ROS during neurogenesis and Prdxs depletion leads to differentiation into neurons [47]. Prdx2 depletion attenuated stemness of CSCs in hepatocellular carcinoma [48]. Prdx3 depletion resulted in a smaller percentage of CD133 + cells, a significant reduction in sphere formation, and enhanced sensitivity to 5-FU [46].…”
Section: Discussionmentioning
confidence: 99%
“…4D) were performed by flow cytometry. Cells in the sub-G1 phase showed fragmented DNA, which is a marker of apoptosis [23, 24]. In our study, the cell cycle analysis showed that cells in the sub-G1 phase and S phase increased in a dose-dependent manner with CG treatment for A549 cells (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…To determine how apoptosis occurs in p53-independent death of NCI-H1299 cells, we examined the generation of ROS, which is a main cause of apoptosis [23, 30]. There are many studies on ROS related to apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Shiota et al [32] demonstrated that PRDX2 increased the growth and castration resistance of prostate cancer by regulating the androgen/androgen receptor signaling pathway. Kwon et al [33] reported that PRDX2 maintains cancer stem cells selfrenewal through VEGF signaling and protects oxidative inactivation of VEGFR2 in hepatocellular carcinoma cells. Stresing et al [19] concluded that inhibiting PRDX2 expression decreased the growth of breast cancer metastatic cells in lungs by specifically regulating the oxidative and metabolic stress response.…”
Section: Discussionmentioning
confidence: 99%